An Analysis of Library Electronic User Satisfaction Using Slims in GKJ Synode with Qualitative Descriptive Method - Kores Enrrique Igglacious Bonsapia; Suprihadi (Jurnal Mantik, 2021)
This research aims to:1) Knowing satisfaction of electronic library users using SLiMS at the GKJ Synod with a qualitative descriptive method.2) Knowing the obstacles faced in implementing SLiMS at the GKJ Synod with a qualitative descriptive method. This research is a type of field research (field research)descriptive. The results showed that:1) System quality satisfaction, namely SLiMS facilitates the work of librarians in managing libraries automatically and helps librarians work; 2) Information quality satisfaction, namely SLiMS is very easy to understand and understand by its users so that it does not take a long time to understand the contents of the information from SLiMS; 3) System usability satisfaction (perceived usefulness); namely SLiMS can complete work quickly and easily because SLiMS makes it easy to manage libraries; 4) Perceived ease of use, namely SLiMS is easy to obtain and easy to use because of its simplicity in appearance and the menus contained therein are quite easy to understand; and 5) Satisfaction of information systems (information systems satisfaction), that is, the output produced by SLiMS corresponds to what already exists in the form of report information that is usually needed in the library.